PENGARUH RASIO AKTIVITAS, RASIO PROFITABILITAS, RASIO LAVERAGE, DAN RASIO PENILAIAN TERHADAP HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGE - Dady Suhadi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
This research is aimed at finding out how the activity ratio, profitability ratio, leverage ratio and evaluation ratio against the stock price of food and beverage manufacture industry. The research design used is correlation research in order to see the influence of the independent variable against the dependent variable with data structure using data pooling which combines data cross sections (20 food and beverage manufacture industries) and time series (2000 2005 period). Double regression method is used to answer research hypothesis by doing several tests i.e. normality test, classic assumption test (multicollinearity, autocorrelation, heterrocsedacity) and theory hypothesis test (R2 Test, Simultaneous Test, and Individual Test). The result of this analysis shows that activity ratio (inventory turnover, assets turnover) and leverage ratio (debt to equity ratio, debt to assets ratio) significantly influences the stock price of food and beverage manufacture industry, while profitability ratio (ROA) and enterprise assessment ratio (EPS and PBV) do not significantly influence the food and beverage manufacture industry.